The Wilful Character of Indigenous Educational Research - Bright, David; Mackinlay, Elizabeth (The Australian Journal of Indigenous Education, 2017)
In her recent work, Sara Ahmed explores wilfulness as a negative charge made by some against others, thinking about the relationship between ill will and good will, the particular and the general, and the embeddedness of will in a political and cultural landscape. In Ahmed's reading, wilfulness is a characteristic often ascribed to those who do ‘not will the reproduction of the whole’ (2011, p. 246) — those who are deemed wayward, wandering, and/or deviant. Using Ahmed's discussions, in this paper, we report on the successes and failures of a research project exploring mentoring programs in enhancing the recruitment and retention of Aboriginal and Torres Strait Islander preservice teachers. We think about the tensions always present between two faces of such a project: the need to reproduce modes of compliance to the expectations of a Western academic institutional regime; and the wilful pursuit of the kinds of wayward resistance and critique that may be potentially undermining and self-sabotaging as well as wholly necessary as attempts at decoloniality. We report on both the successes of the program and the continuing failure to address issues of colonialism. In doing so, we position Aboriginal and Torres Strait Islander research as a performative doubleness which needs wilfulness in order to ‘stand up, to stand against the world’ (Ahmed, 2011, p. 250) of colonial reproduction in neo-liberal times.